Density‐dependent natural selection mediates harvest‐induced trait changes. (28th January 2021) - Bouffet‐Halle, Alix; Mériguet, Jacques; Carmignac, David; Agostini, Simon; Millot, Alexis; Perret, Samuel; Motard, Eric; Decenciere, Beatriz; Edeline, Eric
Abstract: Rapid life‐history changes caused by size‐selective harvesting are often interpreted as a response to direct harvest selection against a large body size. However, similar trait changes may result from a harvest‐induced relaxation of natural selection for a large body size via density‐dependent selection. Here, we show evidence of such density‐dependent selection favouring large‐bodied individuals at high population densities, in replicated pond populations of medaka fish. Harvesting, in contrast, selected medaka directly against a large body size and, in parallel, decreased medaka population densities. Five years of harvesting were enough for harvested and unharvested medaka populations to inherit the classically predicted trait differences, whereby harvested medaka grew slower and matured earlier than unharvested medaka. We show that this life‐history divergence was not driven by direct harvest selection for a smaller body size in harvested populations, but by density‐dependent natural selection for a larger body size in unharvested populations. Abstract : Harvesting is among the most powerful drivers of rapid trait changes in wild populations. It is generally considered that these trait changes result from the action of direct harvest selection against a small body size. We show that these changes may also result from a harvest‐induced relaxation of natural selection for a large body size via density‐dependent selection. This result demonstrates that the effects of natural selection should no longer be ignored in studies or harvest‐induced trait changes.